The European Union's Bilateral Approach - Ludmila Borta (CES Working Papers, 2014)
The EU is a world economic power and a major trading partner for most countries. All the time, this region has been interested and has acted towards a free and fair trade. The decrease and even the elimination of tariff and non-tariff barriers in the world trade are among the main objectives of the EU strategy for international trade. At the moment, the elusive outcome of the WTO Doha Round has led to the proliferation of bilateral trade agreements worldwide. Although the EU remains committed to further development of the multilateral trading system, however, the EU still has appealed also to the development of bilateral trade relations. The aim of this paper is to illustrate the current bilateral dimension of the common commercial policy of the EU. In conclusion, to describe this bilateral approach of the EU we are using one word, namely “diversity”.
Keywords: F13; F19; F53; O52; 330; trade agreement; bilateralism; proliferation; EU's exports/imports; trade barriers